Indicators of sustainable development from the grassroots' perspective - Padilla, Noel O. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2000)
Dimensions of sustainable development were pre-identified from existing literature. Respondents were then interviewed to identify indicators for each sub-dimension of the three dimensions of sustainable development, who then ranked such indicators. The respondents were farmer-cooperators of the Jose Panganiban Agroforestry Project under the Rainfed Resources Development Project (RRDP). The area was chosen since it has shown the elements of sustainable development. The cooperators identified the dimensions of sustainable development to be firstly economic and secondly social and environmental. The sub-dimensions for these dimensions were likewise considered hierarchical except for the environmental dimension.